The effect of negative pressures on the superconductivity of amorphous and crystalline bismuth - Quiroga, Flor B.; Hinojosa-Romero, David; Valladares, Alexander; Valladares, Renela M.; Rodríguez, Isaías; Valladares, Ariel A. (Scientific reports, 2022)
Materials may behave in non-expected ways when subject to unexpected conditions. For example, when Bi was turned into an amorphous phase (a-Bi) unexpectedly it became a superconductor at temperatures below 10 K. Using the superconductivity of the amorphous phase we provided an explanation as to why crystalline bismuth (c-Bi) had not been found to superconduct, and even predicted an upper limit for its superconducting transition temperature T c . This was experimentally corroborated within the following year. We now decided to investigate what happens to the crystalline, Wyckoff structure, and amorphous Bi when pressures below the atmospheric are applied. Here it is shown that, within the BCS approach, under expansion the Wyckoff c-Bi increases its superconducting transition temperature minimally, whereas the amorphous phase decreases its T c . The electron densities of states (eDoS), the vibrational densities of states (vDoS) and the Debye temperatures ( θ D ) are calculated to perform this qualitative evaluation. Expansion can be obtained in the laboratory by chemically etching Bi-based alloys, for example, a process also known as dealloying.